Factors associated with complicated acute appendicitis in a Peruvian pediatric emergency hospital: Factores asociados a apendicitis aguda complicada en un hospital peruano de emergencias pediátricas - Cruz-Zarate, Alberto Manuel (2024)
Introduction: A common onset of acute abdomen that requires a quick operation is appendicitis, since it is more frequent in males than in females, affecting pediatric patients and adolescents from 10 to 20 years of age. There is obstruction of the appendicular lumen, due to fecaliths, hyperplasia of the lymphoid follicle, parasites and primary type carcinomas. Children do not express what they feel and this increases the risk of complications. Objectives: To determine the risk factors associated with complicated acute appendicitis in pediatric patients at the Pediatric Emergency Hospital for the period 2019-2021 Methodology: The study design is analytical, observational, retrospective of cases and controls through data collection from clinical histories and operative reports. Results: A relationship was seen with the following variables: leukocytosis (adjusted OR=2.79 CI=0.95; 1.30 – 6.01 p=0.008), time it takes to go to a major emergency at 24h (adjusted OR=1.72; IC=0.95 1.21-2.45; p=0.003), time from appearance of the first symptom until the surgical act between 24 to 48 hours (adjusted OR=2.25 ; CI=0.95 , 1.14-4.44; p=0.018 ), greater than 49 hours (adjusted OR =3.01; CI:0.95 1.54-5.93 ; p=0.001) with the possibility of developing AAC. Conclusions: The factors related to developing AAC are high leukocyte count, delay in emergency greater than 24 hours, appearance of the first symptom until the surgical act between 24 to 48 hours and greater than 49 hours.